Two calcium‐dependent protein kinases enhance maize drought tolerance by activating anion channel ZmSLAC1 in guard cells. Issue 1 (29th September 2021) - Li, Xi‐Dong; Gao, Yong‐Qiang; Wu, Wei‐Hua; Chen, Li‐Mei; Wang, Yi
Summary: Stomatal closure is an important process to prevent water loss in plants response to drought stress, which is finely modulated by ion channels together with their regulators in guard cells, especially the S‐type anion channel AtSLAC1 in Arabidopsis . However, the functional characterization and regulation analyses of anion channels in gramineous crops, such as in maize guard cells are still limited. In this study, we identified an S‐type anion channel ZmSLAC1 that was preferentially expressed in maize guard cells and involved in stomatal closure under drought stress. We found that two Ca 2+ ‐dependent protein kinases ZmCPK35 and ZmCPK37 were expressed in maize guard cells and localized on the plasma membrane. Lesion of ZmCPK37 resulted in drought‐sensitive phenotypes. Mutation of ZmSLAC1 and ZmCPK37 impaired ABA‐activated S‐type anion currents in maize guard cells, while the S‐type anion currents were increased in the guard cells of ZmCPK35‐ and ZmCPK37 ‐overexpression lines. Electrophysiological characterization in maize guard cells and Xenopus oocytes indicated that ZmCPK35 and ZmCPK37 could activate ZmSLAC1‐mediated Cl ‐ and NO3 ‐ currents. The maize inbred and hybrid lines overexpressing ZmCPK35 and ZmCPK37 exhibited enhanced tolerance and increased yield under drought conditions. In conclusion, our results demonstrate that ZmSLAC1 plays crucial roles in stomatal closure in maize, whose activity is regulated by ZmCPK35 and ZmCPK37. Elevation of ZmCPK35 and ZmCPK37 expression levels is a feasible way to improve maize drought tolerance as well as reduce yield loss under drought stress.